2011
DOI: 10.1227/neu.0b013e31820c6cdc
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Laboratory and Clinical Data Supporting the Safety and Efficacy of Cyclosporin A in Traumatic Brain Injury

Abstract: For decades, cyclosporin A (CsA) has proved to be safe and effective for use in transplantation. In the past 10 years, this agent has shown neuroprotective effects in animal models of traumatic brain injury (TBI). This review article provides a critical overview of the literature on CsA neuroprotective effects in animal studies and current findings of clinical trials in the treatment of TBI with an emphasis on the possible CsA molecular mechanism of action. Animal data provide compelling evidence of the therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Immunosuppressants exert therapeutic benefits by themselves as standalone therapy (i.e. cyclosporine A), even without stem cells, as shown by us and other groups (Tajiri et al, 2016; Osman et al, 2011; Lulic et al, 2011; Ishii et al, 2013; Furuichi et al, 2003). However, most of these therapeutic effects have been observed when immunosuppressants are delivered prior to or immediately after the brain insults in pre-clinical models of CNS disorders.…”
Section: Gene-edited Stem Cellsmentioning
confidence: 69%
“…Immunosuppressants exert therapeutic benefits by themselves as standalone therapy (i.e. cyclosporine A), even without stem cells, as shown by us and other groups (Tajiri et al, 2016; Osman et al, 2011; Lulic et al, 2011; Ishii et al, 2013; Furuichi et al, 2003). However, most of these therapeutic effects have been observed when immunosuppressants are delivered prior to or immediately after the brain insults in pre-clinical models of CNS disorders.…”
Section: Gene-edited Stem Cellsmentioning
confidence: 69%
“…Blast injury, which is a clinically relevant TBI model [12][13][14][15], is technically challenging to recreate in animal models; thus, most TBI approaches focus on a specific type of injury, that is, targeting the cortex [8,[16][17][18][19][20]. The present study offers an alternative model in capturing the clinical scenario of varying injuries in TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cyclosporine-A is safe and tolerable in humans, with at least no negative impact on outcomes or mortality [9091]. Lulic et al have reviewed the shortcomings of the cyclosporine-A preclinical and clinical trials, especially with regard to the heterogeneity of timing of administration of the drug, and have offered guidance for future studies, to clarify the role of cyclosporine in sTBI [104]. …”
Section: Pharmacologic Neuroprotective Strategiesmentioning
confidence: 99%
“…From the standpoint of prognostication, CT grading systems such as the Marshall CT classification [127] and Rotterdam CT score [9] have been incorporated into the IMPACT and CRASH prediction models [104105]. Yet despite the widespread use of head CT in the diagnostic and prognostic evaluation of patients with sTBI, multiple studies have shown that MRI provides higher sensitivity for detecting prognostically relevant intracerebral lesions, particularly traumatic axonal injury[128131].…”
Section: Neuroprognosticationmentioning
confidence: 99%